Numerical study of fatigue crack growth in metallic materials - Pereira, João Ferreira Alves (2023)
Fatigue is the most common failure mode in mechanical components when they are subjected to cyclic loads during their service life. This phenomenon can lead to unexpected and catastrophic failures, even in components that appear to be in good condition. In the context of crack propagation analysis, the relationship between fatigue crack growth rate and the range of the stress intensity factor (da/dN –∆K) is frequently used. However, this approach has limitations regarding the parameter ∆K, as it only quantifies the elastic component at the crack tip. Considering this limitation and since crack propagation is associated with nonlinear and irreversible phenomena at the crack tip, a parameter capable of quantifying the level of plastic deformation, called CTOD (Crack Tip Opening Displacement), was used. In this dissertation, the objective is to study the fatigue crack growth (FCG) in CT specimens using a numerical simulation software based on finite element analysis (Abaqus). Firstly, the study focused on the aluminium alloy AA2024-T351, where the influence of parameters such as specimen’s thickness and size of finite elements in the plane and along the crack front on CTOD and Popen were analysed. Two-dimensional specimens were also created considering plane stress and plane strain states, which were used for comparison with three-dimensional models. Additionally, a comparison of the plastically deformed zones and the crack profile was made among some of the numerical models. Subsequently, a study was conducted on a titanium alloy, aiming to compare the plastic component of ∆CTOD with results obtained from previously conducted experimental tests. It was found that the element size in the plane has some influence on CTOD, especially at the surface, and in Popen as it approaches the mid-thickness of the models. In turn, the element size in thickness only influences the Popen results for zones near the mid-thickness, possibly due to a lower mesh refinement in that area. Another parameter to consider is the thickness of the models, which has shown significant influence on the Popen curves. Regarding case study 2, it was observed that the number of load/unload cycles per propagation greatly influences the results of both CTOD and plastic ∆CTOD, and the discrepancy with respect to the provided experimental results may be due to the assumption of a constant crack propagation rate in the numerical simulations, which is not observed experimentally.